Optimization of BUMDes "Citra Wisata Niaga" empowerment through business management and technology implementation - Irma Nurmala Dewi; Ombi Romli; Dedy Khaerudin (Journal of Community Service and Empowerment, 2025)
Optimisation of village-owned enterprises (BUMDes) "Citra Wisata Niaga" empowerment through business management and technology implementation in Tanara Village, which is a community service within the community-based empowerment scheme, is one application of the TRI DHARMA at Higher Education. With the availability of the PKM DPPM grant from the Ministry of Education, Culture, Research, and Technology in 2025, it is hoped that academics can directly enter the field to understand the difficulties faced by the partner, namely BUMDes "Citra Wisata Niaga" in Tanara Village. The location chosen as a partner in this 2025 service is Tanara Village, Tanara District, Serang Regency, Banten Province. The majority of the population in the Banten region is comprised of farmers, due to the fertile land, and fishermen, largely because of the vastness of the sea and coastal areas. The problems faced by the partners are: 1) not yet using methods and technology in the production process for cutting processed marine fish dough, which is not uniform, 2) lack of knowledge and management skills of BUMDes "Citra Wisata Niaga" regarding economic empowerment of the Tanara community, and 3) marketing or sales methods are still conventional, namely by consigning products to nearby stalls. Therefore, with the grant funded by DPPM Kemendiktisaintek in 2025, which is being carried out by the PKM team from Universitas Bina Bangsa to address partner issues, it is necessary to hold socialisation to improve the marketing of processed seafood in Tanara Village. This activity will be carried out through the transfer of appropriate technology and the handover of a kerupuk cutting machine, enabling the community to utilise this technology in producing for the UMKM BUMDes "Citra Wisata Niaga". The evaluation results obtained are from the socialisation activities on the use of appropriate technology, an increase in consumer interest in processed fish products, such as crackers, and the good and beneficial use of appropriate technology to improve the economy in Tanara Village.